Effect of Xenon on the Phosphorylation of Glycogen Synthase Kinase 3β and Antioxidant Enzymes in Rat Brain - A. N. Kuzovlev; A. I. Shpichko; I. A. Ryzhkov; O. A. Grebenchikov; A. K. Shabanov; Sh. Zh. Khusainov; Z. I. Tsokolaeva; A. V. Lobanov (Неотложная медицинская помощь, 2021)
Relevance. The increase in the number of severe brain injuries due to stroke and traumatic brain injury determines the need to study and develop effective strategies for neuroprotection. The article highlights new mechanisms of the neuroprotective action of the inhalation anesthetic xenon based on the data of our own experimental studies.Aim of study. To assess the effect of anesthesia with xenon at a concentration of 0.5 MAC (minimum alveolar concentration) on the phosphorylation of glycogen synthase kinase 3β (GSK-3β) and the content of antioxidant defense enzymes in the rat brain.Material and methods. The effect of inhalation anesthesia with xenon on the phosphorylation of the GSK-3β enzyme in comparison with lithium chloride, as well as on the content of heme oxygenase, catalase, and Mn-superoxide dismutase in rat brain homogenates was studied by immunoblotting.Results. The use of xenon at a concentration of 0.5 MAA causes an almost twofold increase in the content of the phosphorylated form of the GSK-3β enzyme in comparison with the control (p<0.05) and significantly increases the pool of antioxidant defense enzymes: heme oxygenase by 50% (p <0.05) and Mn-superoxide dismutase by 60% (p<0.05).Conclusion. The conducted experimental study revealed new molecular mechanisms of action of the inhalation anesthetic xenon. The effect of xenon on the pool of enzymes involved in the protection of the brain from oxidative distress was found. The data obtained indicate the prospects for using xenon and require further research in this direction. The use of xenon at a concentration of 50 vol.% (0.5 MAA) for 30 minutes does not affect the content of the glycogen synthase-3β enzyme, at the same time causing an almost twofold increase in its phosphorylated form, the glycogen synthase-3β enzyme, and is accompanied by a significant increase the content of heme oxygenase, Mn-superoxide dismutase and a slight increase in the content of catalase in rat brain homogenates. Thus, the results of the study suggest that one of the possible mechanisms of the neuroprotective effect of xenon is the phosphorylation of glycogen synthase-3β, which prevents the opening of the mitochondrial pore, inhibiting the death of mitochondria-mediated apoptosis of neurons and increasing the level of antioxidant protection in them.